Evaluation of porous β-calcium pyrophosphate as bioresorbable bone graft substitute material. (February 2015) - Lee, K.-S.; Han, H.-S.; Kim, Y.-C.; Lo Han, J. H.; Seung R., H.-; Lee, H.-S.; Chang, J.-S.; Lee, D.-H.
<x content-type="archive" xml:space="preserve">Abstract</x> The osteoconduction of porous bodies made of two kinds of calcium phosphate compounds was investigated by performing single level posterolateral spinal fusions on 20 New Zealand white rabbits. The animals were divided into two groups and implanted with bone graft substitute made of hydroxyapatite (HA) and β-calcium pyrophosphate (β-CPP) respectively. All animals were sacrificed after 12 weeks of surgery, and the fused bone masses were evaluated using manual palpation, uniaxial tensile strength measurement and histological evaluation. Fusion ratios and mean tensile strengths were similar for both β-CPP and HA group. Light and scanning electron microscopy showed new bone growth into the pores, which was abundant in the both β-CPP and HA group. However, the pore size of the β-CPP implant was larger than that of HA, and faster bone growth was observed as β-CPP was absorbed into the host's body. In conclusion, porous β-CPP implants showed more desirable bone graft substitute characteristics due to their satisfactory osteoconductive ability and better biodegradation compared to porous HA implants.